Effect of late season drought stress and different combination of intercropping with barley on yield and yield components of chickpea and faba bean - Hesam Niksirat; Ehsan Bijanzadeh; Roholah Naderi (پژوهش‌های حبوبات ایران)
Introduction A growing interest in intercropping systems has been initiated in developed countries due to the increasing awareness of environmental degradation arising from the heavy use of non-renewable resources such as water. Cereal-legume intercropping are common in natural ecosystems, but now are rarely used in developed countries, except for certain intercropping systems used for animal feed. A renewed interest in intercropping and particularly in intercropping of cereals with legumes has risen again lately. Intercropping can use the available environmental resources more efficiently and thus result in higher yields than monocropping. The reasons for the higher yield in such systems is that the intercropped species do not compete for exactly the same growth resource niche and thereby tend to use the available resources in a complementary way. Izaurralde et al, (1990) used chickpea intercropped with barley in different planting densities and found that grain, straw, and dry matter yields of the mixtures increased with increasing chickpea planting density. With respect to drought stress in late season of Sothern Iran because of cutting off rainfall in this area, and the importance of intercropping to reach stability and sustainability in production, the aim of this study was to assess the changes in yield and yield components of chickpea and faba bean intercropped with barley under late season drought stress.